The scaling of strong field interactions with wavelength - Wilson, Derrek Joseph (Kansas State University, 2018)
Ultrafast laser systems (pulse durations 10-100 femtoseconds) allow for the practical production of intense fields (≥ 10¹³ W/cm²) in a table-top, laboratory setup. The development of this technology has opened the door to studying the interaction of intense laser fields with atoms, molecules, and solid media. These experiments revealed a wealth of dynamics and interplay between the field, ion, and the freed electron, which has led to the production of first attosecond pulses and opened the field of attosecond science. The dynamics of the electron in an intense laser field are fundamental to strong- field phenomena such as higher-order harmonic generation, high energy above threshold ionization, and non-sequential double ionization. As the electron can be strongly accelerated by the instantaneous field, the dynamics depend on both the field's amplitude and wavelength. The latter dependence comes from the fact that the period of the field increases with wavelength. Thus, the electron is accelerated for a longer time and the energy gained is proportional to the wavelength squared. Recent evidence supports the claim that the electron- field interaction at longer wavelengths must include the contribution of the magnetic field and/or the radiation pressure of the field, adding to the wealth of effects associated with strong- field interactions. This thesis explores several routes towards fulfilling gaps in our understanding of the wavelength-scaling of strong- field interactions. I first demonstrate several important developments that reduce the complexity of generating non-sinusoidal, light transient waveforms in the near-infrared, opening the ability to tailor waveforms for more control on strong- field interactions. Next, I demonstrate the development of a strong- field, femtosecond source at wavelengths from 5 micrometers to 9 micrometers. To date, this is the first few-cycle, strong- field (≥ 10¹⁴ W/cm²) source in the long-wave infrared. An important advantage to this design is the wavelength tunability, which provides a control knob for understanding strong- field interactions across a broad wavelength range. Afterwards, I present applications of wavelength tunable sources in strong- field absorption in semiconductors. Specifically, I measure the absorbance of a strong laser field in gallium arsenide as a function of laser polarization, which varies the density of states available to the electron. This is performed for four laser wavelengths spanning 1.2 micrometers to 2.4 micrometers. With these absorbance measurements, we can compare the dependence of the photoexcitation rate on several parameters and compare it to theory. We find that the change in absorbance with density of states deviates from theoretical predictions as the photon order for the photoexcitation increases from two to three. This could be attributed to the field modifying the energy-momentum relationship of the conduction band. To conclude the thesis, I present simulations on a recent experimentally demonstrated technique for amplifying few-cycle electric fields. Due to the difficulty in making these sources, the model I developed includes many of the parameters involved in designing the system. This simulation can be used to plan design criteria, such as nonlinear crystal thickness, for peak performance of the amplification process.
Keywords: Strong-Field Science; Ultrafast Laser Science; Infrared; Intense solid interactions; Wavelength-Scaling Lasers